Serological markers associated with disease behavior and response to anti‐tumor necrosis factor therapy in ulcerative colitis. Issue 1 (January 2015) - Kevans, David; Waterman, Matti; Milgrom, Raquel; Xu, Wei; Van Assche, Gert; Silverberg, Mark
Abstract Background and Aim Information is limited on the relationship between serological markers and disease behavior and anti‐tumor necrosis factor‐α (anti‐TNF) therapy response in ulcerative colitis (UC). This study aimed to determine the association between serological markers and unfavorable UC behavior defined as need for colectomy or UC‐related hospitalization. The association between serological markers and requirement for and outcome of anti‐TNF therapy was also evaluated. Methods Two hundred thirty patients were studied. Requirement for colectomy, UC‐related hospitalization, and anti‐TNF therapy were documented. Response to anti‐TNF therapy at 1 year and rates of therapy discontinuation were recorded. Titers of perinuclear anti‐neutrophil cytoplasmic antibodies (pANCAs), anti‐Saccharomyces cerevisiae antibody (ASCA), and antibody to Escherichia Coli outer membrane porin (anti‐OmpC) were determined. Antibody reference ranges were used to dichotomize subjects into seropositive and seronegative groups. Where multiple tests were performed, P‐values were Bonferroni corrected (pcorr). Results Extensive colitis was associated with requirement for colectomy and UC‐related hospitalization, HR 7.7 (95% confidence interval [CI] 1.9–32.2) pcorr = 0.03 and HR 2.7 (95% CI 1.5–4.6), pcorr = 0.006, respectively. No serological variable was associated with unfavorable UC behavior. Anti‐OmpC positivity was associated with a lack of response to anti‐TNF therapy at 1 year (odds ratio 0.14 [95% CI 0.03–0.60], pcorr = 0.04) and increased likelihood of therapy discontinuation (HR 2.2 [95% CI 1.1–4.7], P = 0.03). Conclusion Extensive colitis is associated with unfavorable disease course in UC. Anti‐OmpC holds promise as a biomarker of anti‐TNF therapy response in UC; however, prospective studies are required before it can be incorporated into routine clinical practice.